2007
DOI: 10.11646/zootaxa.1512.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of the catfish genus Pseudoplatystoma Bleeker  (Siluriformes: Pimelodidae) with recognition of eight species

Abstract: The genus Pseudoplatystoma Bleeker consists of three species long recognized as: P. fasciatum (Linnaeus), P. tigrinum (Valenciennes), and P. corruscans (Spix & Agassiz), and five species recently recognized or described here: P. punctifer (Castelnau), P. reticulatum Eigenmann & Eigenmann, P. orinocoense n. sp., P. metaense n. sp., and P. magdaleniatum n. sp. The eight species form a monophyletic group with two clades that are supported by anatomical features (i.e., skeletal anatomy and myology). One cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
2
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 12 publications
2
75
2
10
Order By: Relevance
“…In some rivers of the Paraguay-Parana River Basin, both species can occur in sympatry (Buitrago-Suárez and Burr, 2007;Langeani et al, 2007). Although several ecological disturbances have constantly affected the wild populations in various localities, especially in the Parana River Basin (Mello et al, 2009), and despite the fact that F1 hybrids have extensively been farmed, posing significant risks to the natural environment, there is a lack of detailed biological studies on hybridisation events involving these species and assessment of artificial hybrid stocks and their impact on wild stocks.…”
Section: Introductionmentioning
confidence: 99%
“…In some rivers of the Paraguay-Parana River Basin, both species can occur in sympatry (Buitrago-Suárez and Burr, 2007;Langeani et al, 2007). Although several ecological disturbances have constantly affected the wild populations in various localities, especially in the Parana River Basin (Mello et al, 2009), and despite the fact that F1 hybrids have extensively been farmed, posing significant risks to the natural environment, there is a lack of detailed biological studies on hybridisation events involving these species and assessment of artificial hybrid stocks and their impact on wild stocks.…”
Section: Introductionmentioning
confidence: 99%
“…This accidental admixture of two species under P. punctifer might have led Buitrago-Suarez and Burr (2007) to erroneously consider that P. fasciatum is not present in the Amazon but only restricted to the Guyanas, and to consider that only P. punctifer is present in the Amazon basin. This could account for why three independent molecular studies (Torrico et al 2009;Carvalho-Costa et al 2011;present study) were not able to genetically differentiate between P. fasciatum and the P. punctifer with black and white stripes (our cluster-1, and the most abundant in nature) described in Buitrago-Suarez and Burr (2007). From the available data, it appears that P. fasciatum might correspond to our cluster-1 and that the species described by Castelnau (1855) as Platystoma punctifer might correspond to our cluster-2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We collected all the specimens found with uncommon color pattern but only some specimens presenting the common pattern (see Buitrago-Suarez and Burr 2007). In doing so, we gave a higher representation to specimens with rare patterns in the sampling.…”
Section: Samplingmentioning
confidence: 99%
“…While we follow the taxonomy of Buitrago-Suárez and Burr (2007), we also consider the possibility that P. reticulatum Eigenmann & Eigenmann, 1889 is a junior subjective synonym of P. fasciatum (Linnaeus, 1766) in light of the study of Carvalho-Costa et al (2011). These authors reported minimal genetic differentiation among the taxa considered conspecific with P. fasciatum previous to the study of Buitrago-Suárez and Burr (2007).…”
Section: Checklistsmentioning
confidence: 98%
“…Identification to species level follows Buitrago-Suárez and Burr (2007) based on the following characters: head strongly depressed with extended cranial fontanelle; loop-like dark bars forming reticulated pattern which extends far below lateral line and connects dorsally; no clear demarcation between dark dorsal and pale ventral regions; and caudal fin with fewer than 45 spots.…”
Section: Checklistsmentioning
confidence: 99%